IJCM_106A: Motivating factor, Health and Quality of life: A mixed methods study of elderly residents in a senior living facility in Bangalore, South India - Prakash Savinitha; Agrawal Twinkle; Stephan Milind; Koshy Karan Anil; George Sukrutha (Wolters Kluwer Medknow Publications, 2024)
Background: Senior living communities, offering autonomous living in India are nascent but are experiencing increased demand due to a growing proportion of financially independent seniors and the prevalent phenomenon of nuclear families. Objective: To determine factors influencing elderly citizens choosing to live in a senior living community, to assess their quality of life, mental health and sleep hygiene; and to qualitatively explore contributing factors. Methodology: This mixed methods study was done exploratively among residents of a private paid-for senior living facility in Bangalore. Quantitative data was collected using standard questionnaires. Linear and logistic regression was performed to look for associations. Subsequently, key informant interviews were conducted. The data were manually coded, and inductive thematic analysis was performed. Results: The median age of the 100 participants was 76 years and 73% were financially independent. Comorbidities were present in 89% of them. Reasons for living in the facility were lack of family support (69%) and preferring to live with peers (13%). The Old People Quality of Life Brief Questionnaire revealed a median score of 44 with 88% strongly agreeing that they enjoyed their life overall. Quality of life was significantly lesser in those lacking family support. Screening for psychological distress using PHQ4 was positive in 22%. Sleep disturbance was perceived by 71%, with waking up in the middle of the night being the commonest complaint. Qualitative findings revealed that the management allocates funds effectively for the residents needs and well-being. Residents stated that staff worked with patience and compassion. Regular recreational activities enhance mental health. Shared religious and social ties foster support. Conclusion: Most residents of this senior living facility said they have a good quality of life and that they were satisfied with the community support and facilities provided.